Making a detour

Calculus Level 4

C x ( x 2 + y 2 ) 3 / 2 d x + y ( x 2 + y 2 ) 3 / 2 d y \int_C\frac{x}{(x^2+y^2)^{3/2}}dx+\frac{y}{(x^2+y^2)^{3/2}}dy

If C C is the path defined by x = 2 t cos ( 2 π t 2 ) , y = 2 t sin ( 2 π t 2 ) x=2^t\cos(2\pi t^2), y=2^t\sin(2\pi t^2) , for 0 t 1 0\leq t\leq 1 , find the integral above.


The answer is 0.5.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Abhishek Sinha
Feb 28, 2016

The integral may be written as 1 2 C d ( x 2 + y 2 ) ( x 2 + y 2 ) 3 / 2 = 1 x ( 0 ) 2 + y ( 0 ) 2 1 x ( 1 ) 2 + y ( 1 ) 2 = 1 2 \frac{1}{2} \int_C \frac{d(x^2+y^2)}{(x^2+y^2)^{3/2}} = \frac{1}{\sqrt{x(0)^2+y(0)^2}}-\frac{1}{\sqrt{x(1)^2+y(1)^2}}=\frac{1}{2} Remark: Since the integrand is an exact differential , its integral does not depend on the whole path of integration; only the initial and the final points matter.

Yes, exactly (pun intended)! (+1)

For the members who are not so familiar with the subject, we should point out that a potential of the given 1-form ω = x ( x 2 + y 2 ) 3 / 2 d x + y ( x 2 + y 2 ) 3 / 2 d y \omega=\frac{x}{(x^2+y^2)^{3/2}}dx+\frac{y}{(x^2+y^2)^{3/2}}dy is f ( x , y ) = 1 x 2 + y 2 f(x,y)=-\frac{1}{\sqrt{x^2+y^2}} , meaning that d f = f x d x + f y d y = ω df=\frac{\partial f}{\partial x}dx+\frac{\partial f}{\partial y}dy=\omega . As you say, the integral depends only on the initial point A = ( 1 , 0 ) A=(1,0) and the terminal point B = ( 2 , 0 ) B=(2,0) of the path C C ; it is "path-independent". Then C d f = f ( B ) f ( A ) = 1 2 \int_C df=f(B)-f(A)=\frac{1}{2} .

For those who are familiar with single-variable calculus only: The potential f f plays the role of an antiderivative, and C d f = f ( B ) f ( A ) \int_C df=f(B)-f(A) is a version of the fundamental theorem, analogous to the single-variable case.

In terms of physics, we are looking at an inverse square field here that could represent a gravitational field, while f ( x , y ) f(x,y) could represent the gravitational potential energy (up to a constant multiple, of course).

Otto Bretscher - 5 years, 3 months ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...